2000
DOI: 10.1046/j.1472-765x.2000.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

The viable but non-culturable state of wine micro-organisms during storage

Abstract: V . M IL L ET AN D A. LO N VA UD -FU NE L . 2000. Colony counting and DEFT did not give the same results when wine micro-organisms were enumerated. Both methods were used to monitor the population of acetic acid bacteria (AAB) and lactic acid bacteria (LAB) during wine storage. Results suggest that part of the populations had reached a viable but non-culturable (VBNC) state. These cells were unable to produce colonies but could hydrolyse fluorescent esters and could be counted by DEFT. For AAB, O 2 deprivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(163 citation statements)
references
References 12 publications
7
152
1
3
Order By: Relevance
“…Low recovery of strains due to the fraction of population that could reach a viable but non-culturable (VBNC) state has been stated. For instance in wine it was shown that VBNC status of spoiling AAB is induced by O 2 deprivation [32]. Whereas in vinegars some studies developed by no culture approaches, such as PCR/DGGE, revealed higher species diversity respect to that detected by culturing methods [3,33,34].…”
Section: Isolation and Cultivabilitymentioning
confidence: 99%
“…Low recovery of strains due to the fraction of population that could reach a viable but non-culturable (VBNC) state has been stated. For instance in wine it was shown that VBNC status of spoiling AAB is induced by O 2 deprivation [32]. Whereas in vinegars some studies developed by no culture approaches, such as PCR/DGGE, revealed higher species diversity respect to that detected by culturing methods [3,33,34].…”
Section: Isolation and Cultivabilitymentioning
confidence: 99%
“…To test the strains in an enology context, the synthetic medium was close to a wine at the final phase of alcoholic fermentation (but without any polyphenols). Total cell numeration was chosen to avoid under-evaluating the population in regard to cells in a viable but non-cultivable state (viable and active cells that are not able to grow on classical solid medium), since this is often the case in long term cultures and under stressful conditions such as in alcoholcontaining medium 7,25 . Moreover, high metabolic activity was noted until the end of the experiments.…”
Section: Behaviour During Fermentationmentioning
confidence: 99%
“…Traditionally, culture-based enrichment methods are used for detection and identification of yeasts in wine, but these methods can be time-consuming and can misrepresent the community present by biasing for the growth of less fastidious organisms (Heard and Fleet 1986), and the occurrence of viable-but-not-culturable (VBNC) cells in the low-pH, highethanol environment of wine can limit the sensitivity of these methods (Millet and Lonvaud-Funel 2000). To surmount these issues, culture-independent methods for comprehensively profiling wine microbiota have received more attention, with denaturing gradient gel electrophoresis (DGGE) the most popular (Cocolin et al 2000, Mills et al 2002.…”
mentioning
confidence: 99%